Polycrystalline thin films of antimony selenide via chemical bath deposition and post deposition treatments - Rodríguez Lazcano, Yamilet; Peña Méndez, Yolanda; Nair Maileppallil, Santhamma; Nair Padmanabhan, Karunakaran (Centro de Investigación en Energía, Universidad Nacional Autónoma de México, 2005)
We report a method for obtaining thin films of polycrystalline antimony selenide via chemical bath deposition followed by heating the thin films at 573 K in selenium vapor. The thin films deposited from chemical baths containing one or more soluble complexes of antimony, and selenosulfate initially did not show X-ray diffraction (XRD) patterns corresponding to crystalline antimony selenide. Composition of the films, studied by energy dispersive X-ray analyses indicated selenium deficiency. Heating these films in presence of selenium vapor at 573 K under nitrogen (2000 mTorr) resulted in an enrichment of Se in the films. XRD peaks of such films matched Sb2Se3. Evaluation of band gap from optical spectra of such films shows absorption due to indirect transition occurring in the range of 1 – 1.2 eV. The films are photosensitive, with dark conductivity of about 2x10-8 (V cm)-1 and photoconductivity, about 106 (V cm)1 under tungsten halogen lamp illumination with intensity of 700 W m2. An estimate for the mobility life time product for the film is 4x10-9 cm2 V-1.